The presence of Fabaceae in the pollen profile of propolis produced in northeastern Brazil - Avelino,Luciano Oliveira (2018)
ABSTRACT Propolis is a resin-like substance composed mainly of resin, wax, essential oils, pollen grains and specific plant parts collected by the honeybee Apis mellifera, which mixes them with fluids they secrete. The components and chemical properties of propolis vary among regions. Therefore, in order assess variation in the botanical composition of propolis, 26 samples of propolis (brown, red, and green) produced throughout northeastern Brazil were analyzed by acetolysis specifically adapted for propolis. In total, 196 pollen types were recorded, representing 123 genera and 47 families, with types of Fabaceae and Rubiaceae being present in 100 % of the samples. Fabaceae was the richest group with 49 pollen types, followed by Malvaceae (10 types), particularly related to the high frequencies of Mimosa pudica (84.62 %), Alternanthera, Borreria verticillata, and Myrcia (80.77 %). Remarkably, 34 % of the pollen types with frequencies above 50 % belonged to Fabaceae, even though this family has been traditionally regarded as less important with regard to propolis production, given that most of its included taxa are classified as polliniferous or nectariferous. Similarity analyses revealed clusters of propolis samples that share pollen types associated with plants having apiculture potential.